Jawāhir al-akhbār : Bakhsh-i tārīkh-i Īrān az Qarāqūyūnlū tā sāl-i 984 hijri-yi qamarī - Qazwīnī, Būdāq Munshi, (Miras Maktoob, ISBN: 9789004365452., 2019)
In medieval Persia, the munshī or court secretary belonged to a highly professional, privileged class, enjoying a comfortable income and attractive living conditions. The better one's style of writing, elegant yet concise, and the more types of document one could draft, in each case using the appropriate format and terminology, combined with the right kind of political intelligence, the higher one would rise in munshī hierarchy. Despite his high social standing, a munshī could find himself without a job overnight if he fell victim to court intrigue or if there was a change in power. The author of the universal history contained in the present volume, Būdāq Munshī Qazwīnī (d. late 10th/16th cent.), who in his lifetime worked as a scribe, secretary, local administrator, assessor, controller, and vizier, lost his job several times precisely for these reasons. Written from personal experience, the history's part on the Safavids is of special interest.